Nanoparticles: Recovery of Drug Delivery Nanoparticles from Human Plasma Using an Electrokinetic Platform Technology (Small 38/2015). Issue 38 (October 2015) - Ibsen, Stuart; Sonnenberg, Avery; Schutt, Carolyn; Mukthavaram, Rajesh; Yeh, Yasan; Ortac, Inanc; Manouchehri, Sareh; Kesari, Santosh; Esener, Sadik; Heller, Michael J.
<x xml:space="preserve">Abstract</x> M. J. Heller and co‐workers describe the use of electrode arrays to collect select nanoparticles from a complex mixture. On page 5088, they explain how their dielectrophoresis collection chip pulls the desired nanoparticles down to the electrode surface, allowing them to be collected from complex fluid mixtures such as biological blood samples. Recovering nanoparticles is a major challenge in many fields, so this technique is expected to find broad interest across the nanoparticle community.